2009
DOI: 10.1109/tits.2009.2032770
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Urban Pedestrian Detection for Automatic Braking

Abstract: This paper presents an application of a pedestrian-detection system aimed at localizing potentially dangerous situations under specific urban scenarios. The approach used in this paper differs from those implemented in traditional pedestrian-detection systems, which are designed to localize all pedestrians in the area in front of the vehicle. Conversely, this approach searches for pedestrians in critical areas only. The environment is reconstructed with a standard laser scanner, whereas the following check for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(76 citation statements)
references
References 14 publications
0
74
0
2
Order By: Relevance
“…The automatic intervention of typical AEB systems aims to improve on the reaction of the driver, even when the collision is inevitable and the benefit of the system is injury mitigation rather than prevention. The development of advanced detection systems will further improve the robustness of the target-recognition algorithms and boost reaction time in particularly challenging scenarios such as small, fast moving targets emerging from visual obstructions (Broggi et al, 2009). For such extreme scenarios, the test configurations corresponding to STATS19 cluster 2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The automatic intervention of typical AEB systems aims to improve on the reaction of the driver, even when the collision is inevitable and the benefit of the system is injury mitigation rather than prevention. The development of advanced detection systems will further improve the robustness of the target-recognition algorithms and boost reaction time in particularly challenging scenarios such as small, fast moving targets emerging from visual obstructions (Broggi et al, 2009). For such extreme scenarios, the test configurations corresponding to STATS19 cluster 2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Side impacts were filtered from the study to accommodate the current capability of AEB systems which are designed to detect pedestrians in front of the vehicle within a range defined as the driving corridor (Broggi et al, 2009). In addition it has been shown that head injuries incurred by pedestrians in side impacts are mainly caused by impact with the road or ground rather than impact with the vehicle (Badea-Romero and Lenard, 2013), indicating the limitations of safety technology for this form of interaction between vehicles and vulnerable road users.…”
Section: Methodsmentioning
confidence: 99%
“…These measures may include autonomous emergency braking or autonomous steering (e.g. Broggi et al, 2009;Hayashi et al, 2012;Keller et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…A lidar alone can be used to estimate the ego-motion and to detect mobile objects thanks to a dense 3D grid-map approach [4]. In [5] and [6] real time sensor-referenced approaches (i.e. ego-localization is not considered) are presented using multi-sensor systems showing the complementarity of lidar and vision systems in automotive applications.…”
Section: Introductionmentioning
confidence: 99%